Knowledge and perceptions of potential factors contributing to birth asphyxia in a selected mother and child hospital in Gauteng Province - Musie, Maurine Rofhiwa (University of Pretoria, 2023)
Dissertation (MNur (Nursing Science))--University of Pretoria, 2023.